2013
DOI: 10.1364/ao.52.006626
|View full text |Cite
|
Sign up to set email alerts
|

Thermal response of a dental tissue induced by femtosecond laser pulses

Abstract: This paper reports a theoretical and experimental study for thermal transport in a thin slice of human tooth induced by a 120 fs, 800 nm pulse laser at a repetition rate of 1 kHz. The surface reflectivity of enamel and the convection heat transfer coefficient were determined using an inverse heat transfer analysis. Instead of a fully three-dimensional modeling, two simplified two-dimensional (2D) planar and axisymmetric heat conduction models were proposed to simulate the temperature fields. The temperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition to the structural support provided by the scaffold nanofibrils, which likely contributed to improved graft survival and integration, were the benefits of tissue-specific scaffold presentation of the functional laminin epitope, IKVAV. Previous studies have reported IKVAV, the motif from the a1 chain of the laminin-1 peptide sequence, promotes neuronal cell attachment, migration, differentiation, and neurite outgrowth (Cheng et al, 2013;Silva et al, 2004;Tashiro et al, 1989), including that of hESC-derived neurons (Ma et al, 2008). In support, here, we report enhanced neuronal specification of hESC-derived neural grafts in the presence of the IKVAV scaffold, as well as augmented deep (TBR1) and superficial (BRN2) cortical layer specification of NPCs, necessary for the replacement of neurons lost to the primary insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the structural support provided by the scaffold nanofibrils, which likely contributed to improved graft survival and integration, were the benefits of tissue-specific scaffold presentation of the functional laminin epitope, IKVAV. Previous studies have reported IKVAV, the motif from the a1 chain of the laminin-1 peptide sequence, promotes neuronal cell attachment, migration, differentiation, and neurite outgrowth (Cheng et al, 2013;Silva et al, 2004;Tashiro et al, 1989), including that of hESC-derived neurons (Ma et al, 2008). In support, here, we report enhanced neuronal specification of hESC-derived neural grafts in the presence of the IKVAV scaffold, as well as augmented deep (TBR1) and superficial (BRN2) cortical layer specification of NPCs, necessary for the replacement of neurons lost to the primary insult.…”
Section: Discussionmentioning
confidence: 99%
“…Use of biomaterials is increasingly being recognized as a valuable adjunct approach for cell-based therapies and may impart physical and trophic support to both host and grafted cells (Jendelová et al, 2016). A variety of natural and synthetic polymers, such as collagen, chitosan, and poly(lactic acid), as well as decellularized scaffolds, have been employed to support neural grafts in the ischemic brain (Bible et al, 2009(Bible et al, , 2012Cheng et al, 2013;Elias and Spector, 2012;Jin et al, 2010;Liang et al, 2013;Park et al, 2002;Yu et al, 2010;Zhong et al, 2010). While these materials have shown variable anatomical and functional benefits, most optimal for regenerative medicine will be the employment of readily injectable nanomaterials that self-assemble from biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The k cat values determined for each of the wild type NBD constructs in this study (Table 3) are lower than those measured by Sevier and colleagues, 48 however the k cat and K M values we found are consistent with the range of previously reported k cat (0.83 -0.031 min −1 ) and K M (270 -0.11 μM) values for either isolated NBDs or full-length Hsp70s. 49,[55][56][57][58][59][60][61] The diseaseassociated mutations severely impaired catalytic activity of mortalin-NBD (Figure 7). R126W mortalin-NBD exhibited a ~65% decrease in the catalytic activity and 30% weaker K M of 230 ± 50 μM compared to the wild type mortalin-NBD.…”
Section: Impaired Atp Hydrolysis For Even-plus Syndrome Mortalin Mutantsmentioning
confidence: 99%
“…Though there are numerous experimental studies attempt to predict the laser ablation profile are quite far and few. 15,18,26 Most of the studies [27][28][29][30][31][32] are computational model which requires complete knowledge of thermophysical properties and extensive computational resources. 5 Even computational models are tractable only for homogeneous materials like metal, the difficulty in incorporating heterogeneity of the teeth make these models unreliable.…”
Section: Introductionmentioning
confidence: 99%